2015
DOI: 10.18632/oncotarget.6506
|View full text |Cite
|
Sign up to set email alerts
|

The positive prognostic effect of stromal CD8+ tumor-infiltrating T cells is restrained by the expression of HLA-E in non-small cell lung carcinoma

Abstract: INTRODUCTIONTumor-infiltrating CD8+ T cells are associated with improved clinical outcomes in non-small cell lung cancer (NSCLC). Here we studied their prognostic effect in the context of the expression of HLA molecules that are key in tumor recognition (HLA-A, B and C) or suppression of immunity (HLA-E) as this is still unknown.METHODSTumor tissue of 197 patients with resected pulmonary adenocarcinoma was analyzed for the presence of CD8+ T cells and the expression of β2-microglobulin, HLA-A, HLA-B/C and HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…We and others reported a negative correlation of HLA-E on the overall survival of cancer patients (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011); in particular, the beneficial effect of high CD8 T cell counts within tumor was mitigated by high protein expression of HLA-E (Talebian Yazdi et al, 2016, Gooden et al, 2011). These findings suggested that NKG2A receptor expression on tumor-infiltrating lymphocytes might hamper their function by interaction with HLA-E in the microenvironment.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We and others reported a negative correlation of HLA-E on the overall survival of cancer patients (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011); in particular, the beneficial effect of high CD8 T cell counts within tumor was mitigated by high protein expression of HLA-E (Talebian Yazdi et al, 2016, Gooden et al, 2011). These findings suggested that NKG2A receptor expression on tumor-infiltrating lymphocytes might hamper their function by interaction with HLA-E in the microenvironment.…”
Section: Introductionmentioning
confidence: 66%
“…HLA-E is ubiquitously expressed at low levels, but very high expression can be found on trophoblasts and ductal epithelial cells in immune-privileged tissues like placenta and testis, respectively. In cancers, HLA-E is frequently overexpressed compared to their non-transformed counterparts, including melanoma and carcinomas of lung, cervix, ovarium, vulva and head/neck (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011). The physiological function of HLA-E is to present ‘self’ peptides derived from other HLA class I molecules (DeCloux et al, 1997, Kraft et al, 2000, O’Callaghan et al, 1998) and to limit autoimmune reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The function of Qa-1b/HLA-E in tumour immunity has been unclear, because it can bind to both activating and inhibitory receptors expressed by T cells and NK cells 16,22 , and because it has been variously reported to be associated with good or bad clinical outcomes 23,24 . Loss of function of Qa-1b may increase the immune response to tumours by de-repression of T- or NK-cell function 25,26 or by limiting the stimulation of CD8 + T regulatory cells 27 , either of which would make blockade of HLA-E an attractive immunotherapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies have already shown that occurrence of autoimmunity, a systemic chronic inflammation profile, as well as the level of tumor infiltration by different lymphocyte subsets and macrophages, may indeed predict the outcome of patients with different disease including non small cell lung cancer (NSCLC), colorectal carcinoma (CRC), breast cancer, melanoma and other malignant diseases. [16][17][18][19][20][21][22][23][24][25] In particular, the results of previous studies by our group showed that primary tumor infiltration by immune-regulatory T cells (CD25 , namely T cm ) are associated to a prolonged PFS and OS in patients with metastatic colorectal carcinoma undergone frontline chemotherapy. [26][27][28] On these bases, we investigated whether infiltration of the primary tumor by different lymphocyte subsets may predict the outcome of PC patients.…”
Section: Introductionmentioning
confidence: 92%